Cetuximab Plus Methotrexate in Recurrent and/or Metastatic Head-and-Neck Squamous Cell Carcinoma - Wen-Chen Tang; Pei-Wei Huang; Chien-Yu Lin; Chia-Hsun Hsieh; Cheng-Lung Hsu; Shiang-Fu Huang; Chun-Ta Liao; Chih-Hua Yeh; Nai-Ming Cheng; Hung-Ming Wang* (Journal of Cancer Research and Practice)
Background: The effectiveness of cetuximab (CTX) combined with methotrexate (MTX) has not yet been evaluated in patients with recurrent and/or metastatic head-and-neck squamous cell carcinoma (RM-HNSCC). Materials and Methods: A retrospective analysis of patients with RM-HNSCC who received 50 mg MTX weekly plus a standard dose of CTX for a maximum of 18 weeks, without maintenance CTX. Results: A total of 164 patients were included (cisplatin-sensitive, 88; cisplatin-refractory, 76). Among 58 cisplatin-sensitive patients receiving CTX/MTX as the first-line treatment, the outcomes were 39.7% response rate (RR), 70.7% disease control rate (DCR), 6.0 months of median progression-free survival (PFS), and 9.0 months of overall survival (OS). Among cisplatin-refractory patients, results were 31.6% RR, 51.3% DCR, 4.0 months of PFS, and 6.0 months of OS. Multivariable analyses revealed PFS and OS were not associated with cisplatin-refractory status, age, performance status, or the lines of CTX/MTX treatments. In cisplatin-refractory patients, those with only locoregional-recurrence disease had significantly worse PFS, but this did not affect OS; a similar trend was observed in cisplatin-sensitive patients. Conclusion: A CTX/MTX regimen, without maintenance CTX, is a safe and effective palliative treatment for both patients with cisplatin-sensitive or cisplatin-refractory RM-HNSCC. The low adverse events and easy administration makes this treatment a suitable option in various contexts, particularly for cisplatin-unfit or frail patients with RM-HNSCC.